Model Pembangunan Infrastruktur Sosial Berbasis Komunitas Melalui Integrasi Nilai-Nilai Filantropi Hindu di Bandar Lampung - Ketut Angga Irawan (Jayapangus Press, 2026)
Social infrastructure development in Indonesia remains dominated by a top-down approach that limits community participation. This study aims to analyze the integration of Hindu philanthropic values in community-based social infrastructure development in Bandar Lampung. A qualitative descriptive method was employed through in-depth interviews, observation, and document analysis involving Hindu religious leaders, PHDI, PERADAH, KMHDI, and academics. The findings indicate that the values of dāna, seva, and karma yoga are integrated into deliberative decision-making, transparent community fund management, and intergenerational participation, thereby strengthening social cohesion, accountability, and a sense of community ownership over social infrastructure. In addition, the integration of Hindu philanthropic values contributes to the preservation of cultural identity and the sustainability of community social practices. This study concludes that Hindu philanthropy functions as a sustainable social system that supports participatory governance and inclusive community-based infrastructure development.